Characteristics of women seeking care at a vulvar clinic: A study of 600 patients during a 17‐year period - Karolina Rosendahl; Alexander Shayesteh; Elisabet Nylander (Wiley, 2023)
Abstract Background Symptoms from the vulva and vagina affect about one‐third of all women and have a negative influence both on sexual health and psychosocial well‐being. Research regarding vulvar diseases is sparse and there is a need for a better understanding of women seeking care for vulvar diseases. Objectives The objectives of this descriptive study were to investigate symptoms, signs, and background characteristics of women attending our multidisciplinary vulvar clinic at the University Hospital, Umeå, Sweden between 2005 and 2021. Methods We conducted a prospective study by using a vulvar‐specific questionnaire and reviewed the medical records to collect supplementary data. Results A total of 600 women participated. The most common symptom among all participants was dyspareunia (67.6%). Pain diagnoses dominated in the younger population while inflammatory diseases were most common among patients 40 years of age or more. We found a significant association between dyspareunia and negative experiences of gynaecological examination (p < 0.001) as well as between pruritus and not having a regular contact with a psychologist (p < 0.05). Conclusions Women seeking care at our vulvar clinic exhibit a complicated and complex set of symptoms intertwined with many aspects of life. Increasing awareness among healthcare professionals, an experienced team at the clinic, and a multidisciplinary approach regarding the symptoms and needs of women with vulvar conditions are important to optimise care and treatment. Clinicians must be aware that vulvar diseases may have different symptomatology due to age. It is also important to highlight that the symptomatology presented by patients attending for vulvar diseases, has changed during the past decade.